2017
DOI: 10.1080/17458080.2017.1321793
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of magnetic crosslinked starch-graft-poly(acrylamide)-co-sodium xanthate and its application in removing heavy metal ions

Abstract: This paper describes the synthesis and characterisation of a magnetic crosslinked starch-graft-poly(acrylamide)-co-sodium xanthate (M-CSAX) nanocomposite based on magnetic starch (MCS), acrylamide (AM) and sodium xanthate that underwent heavy metal ions removal in response to an external magnetic field. The material was prepared using magnetic particle Fe 3 O 4 nanoflakes (NFs) together with vinylated starch and poly(acrylamide)-cosodium xanthate via an ultrasound-assisted radical crosslinking/ polymerisation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…In general, the composites prepared with the resin Dowex 50 WX4 were the most efficient in the removal of Ni(II), Cu(II), Cd(II) and Pb(II), showing an adsorption capacity of 384, 416, 398 and 380 mg/g, respectively [45]. These values are higher than the data registered for other composites obtained from carbon nanotubes [34], α-cellulose [40], chitosan [41][42][43], silica [53], starch [54] and different types of biomass such as waste orange peel, pine bark and Cyclosorus interruptus (see Table 3) [33,50,55]. Additionally, it is relevant to mention that for the removal of Cr(VI), the composite obtained with poly(vinylidene fluoride) shows the higher adsorption capacity (1423.4 mg/g) in comparison with the samples prepared from chitosan (46 mg/g), cotton (3.74 mg/g) and Dowex 50 WX4 resin (400 mg/g) [41,44,45].…”
Section: Magnetic Adsorbentsmentioning
confidence: 99%
“…In general, the composites prepared with the resin Dowex 50 WX4 were the most efficient in the removal of Ni(II), Cu(II), Cd(II) and Pb(II), showing an adsorption capacity of 384, 416, 398 and 380 mg/g, respectively [45]. These values are higher than the data registered for other composites obtained from carbon nanotubes [34], α-cellulose [40], chitosan [41][42][43], silica [53], starch [54] and different types of biomass such as waste orange peel, pine bark and Cyclosorus interruptus (see Table 3) [33,50,55]. Additionally, it is relevant to mention that for the removal of Cr(VI), the composite obtained with poly(vinylidene fluoride) shows the higher adsorption capacity (1423.4 mg/g) in comparison with the samples prepared from chitosan (46 mg/g), cotton (3.74 mg/g) and Dowex 50 WX4 resin (400 mg/g) [41,44,45].…”
Section: Magnetic Adsorbentsmentioning
confidence: 99%
“…The starch can be easily restored through weak acidic washing, and the success of metal removal depends on avoiding highly acidic metal solutions. Increasing the levels of carboxymethylation and cross-linking can enhance the metal scavenging activity of starch, making it suitable for industrial applications [ 62 , 64 , 155 , 156 , 157 ].…”
Section: Applications For Water Treatmentmentioning
confidence: 99%
“…In the study by Wang et al, it was reported that an increase in the dosage of the BNCs resulted in a 78.3% increase in the removal of Pb (II) and a 63% increase in the removal of Cu (II). The availability of additional sorption sites and increased surface area with increasing BNC dosage resulted in better elimination of these MI [78].…”
Section: Factors Affecting Sorption Of Hms and Dyes Using Bncsmentioning
confidence: 99%